HASIL DESTILASI KERING KAYU DAN NILAI KALOR DARI BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Nurmala Hudaya; Hartoyo Hartoyo (Jurnal Penelitian Hasil Hutan, 1988)
Rapid  destructive distillation  of  20  Industrial Forest  Plantation Timber  Species  was carried out  by  using a  retort equipped with electrical heating system. This retort was also  connected to  three  condensors and  two  flask   to  catch and  collect  the  distillate  or  condensed   gas.  The  retort capacity was about 4  kg  of  wood.Treatment  conditions    given  in  these  experiment  were  maximum  heating   temperature    of  500°C  and  5  hours distillation time.The product   (charcoal, tar,  pyroligneous liquor) of  the  destructive  distillation   of  wood  showed  a wide variation  in yield   or  composition  depending on  the  wood  species,  age and  growth   location.This  experimental  condition produces   charcoal yield  varying  from  21,38 - 38,00%,   tar from  4.99 - 13.78% and pyroligneous liquor  from  44.91 -  157.17%. Pyroligneous liquor  product  can  be used  as disinfectant,  weed  killer and deodorant. Tar product has a good  prospect  for  wood  preservative  subtance  and  medicinal.The  destructive distillation  of  wood  under   these  experimental conditions produced brittle  and  light  charcoal.  On the  contrarary, hard charcoal  could  be produced from  slower  pyrolisis  process  in a commercial   scale.Proximate analyses  of  charcoal  obtained   from   these  experiments  revealed  that  the  quality  IS  suitable  for both  as raw  material   for  commercial   activated   carbon  and  fuel.Calorific  values of  wood  ranged  from  4285  to  4994  kcal/kg  and  charcoal  from  6746  to  7748  kcal/kg. Based  on  these  calorific  values,  wood  and  charcoal  of  the  20  wood  species  observed  are excellent material  to  be used as fuel.